Substantiating the Relevance of Worklife Balance in Human Resource Management: A Literary Perspective - Shukla, P; Chakraborty, SS (International Journal of Computer Sciences and Engineering, 2025)
Achievement can be viewed as motive of life while enjoyment is the fuel that drives that motive. Work cultures have often demanded a transformation from inflexibility to flexibility. There is a life at work and at home and also a life having space for leisure. With globalization becoming the norm of the day, these issues seem to have taken a back seat for quite a while. Worklife 'imbalance' has over a period of time attracted concern because of increasing problems related to employee health, monotony at work place, declining levels of productivity and efficiency at the employee level. This paper aims to substantiate the appositeness of Worklife balance in human resource management as a crucial management function